2017
DOI: 10.1016/j.nefro.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury due to excessive and prolonged intramuscular injection of veterinary supplements containing vitamins A, D and E: A series of 16 cases

Abstract: Excessive use of veterinary vitamin supplements containing high doses of vitamin A, D and E was associated with AKI. Hypercalcaemia, which was a common finding, appears to be a contributing factor to the development of this type of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…While hypercalcaemia has been known to cause AKI for many decades in a variety of presentations such as malignancies, sarcoidosis, milk alkali syndrome, vitamin D overdose, hyperparathyroidism and hyperthyroidism, [26][27][28][29][30] the estimated risk of AKI following hypercalcaemia was unclear. Our study demonstrated that elevated calcium levels on admission were associated with a 1.51-fold increased risk of in-hospital AKI.…”
Section: Discussionmentioning
confidence: 99%
“…While hypercalcaemia has been known to cause AKI for many decades in a variety of presentations such as malignancies, sarcoidosis, milk alkali syndrome, vitamin D overdose, hyperparathyroidism and hyperthyroidism, [26][27][28][29][30] the estimated risk of AKI following hypercalcaemia was unclear. Our study demonstrated that elevated calcium levels on admission were associated with a 1.51-fold increased risk of in-hospital AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney disease has been reported among AAS users, but only in individuals with significant kidney damage (3,8). The discovery of novel biomarkers has a great importance for early detection of kidney disease and allows the adoption of measures to prevent or slow kidney disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Renal function abnormalities are described among AAS users, usually when supra-physiologic doses are used, including the use of veterinary supplements (3,8). One of the mechanisms that have been proposed for kidney injury in these cases is the excess use of vitamin D, leading to hypercalcemia, hypercalciuria and nephrocalcinosis (8,20).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…compounds is practiced in South America and the Middle East with an apparently high frequency of end-stage renal disease (ESRD) [2,3,4].…”
mentioning
confidence: 99%